Development of Virtual Reality (VR)-Based “Jelajah Geometri” Animation Media to Improve Critical Thinking Skills of Grade IV Elementary School Students - Wahyuningrum, Fanny; Arifuddin, Ahmad; Andini, Wulan; Firdaus, Fery Muhamad (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2025)
This research aims to understand the development process of the "Jelajah Geometri" animation media based on virtual reality (VR) to enhance critical thinking skills in fourth-grade elementary school students, as well as to determine the students' responses after using the "Jelajah Geometri" animation media based on virtual reality (VR) to improve critical thinking skills in fourth-grade elementary school students on the topic of composition and decomposition of flat shapes. This research was conducted at SDN Penggung I, involving 20 fourth-grade students as respondents. The method used in this research is Research and Development (RD) based on the ADDIE development model, which consists of five main stages: 1) Analysis, 2) Design, 3) Development, 4) implementation, and 5) Evaluation. Based on the validation results from the expert team, the media feasibility levels are as follows: media expert 96%, language expert 100%, and material expert 95%, all of which fall into the very valid category. After revisions were made to the media and materials according to the suggestions from the validators, the researcher proceeded to the implementation stage, or trial, with 20 fourth-grade students. The implementation results indicate  that the media received a score of 76%, which falls into the "good" category.